2012
DOI: 10.1001/archoto.2012.1778
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in the Treatment of a Pediatric Midline Neck Mass

Abstract: Ultrasonography is helpful in determining the pediatric midline neck masses that need to be removed surgically. It is less helpful in determining the exact pathologic characteristics of the lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…Anterior neck masses in children are most commonly TGDC, DC, or reactive lymph nodes. Ultrasonography is preferred over computed tomography and magnetic resonance imaging for evaluation of these masses in children because it is less expensive, has no ionizing radiation, is noninvasive, and does not require sedation . Although ultrasound is quite good at differentiating cystic (TGDC and DC) from solid (lymph node) structures based on density and blood flow, historically, it has not proven very useful for differentiating TGDC from DC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anterior neck masses in children are most commonly TGDC, DC, or reactive lymph nodes. Ultrasonography is preferred over computed tomography and magnetic resonance imaging for evaluation of these masses in children because it is less expensive, has no ionizing radiation, is noninvasive, and does not require sedation . Although ultrasound is quite good at differentiating cystic (TGDC and DC) from solid (lymph node) structures based on density and blood flow, historically, it has not proven very useful for differentiating TGDC from DC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have described ultrasound characteristics of TGDC as being well‐circumscribed, homogenous, posteriorly enhancing cysts located above the level of the thyroid gland; and they have described DC as being well‐circumscribed, thin‐walled, heterogeneous cysts . Unfortunately, this ultrasound distinction has not been consistent in the literature . Some studies presented conflicting results and others suggested that ultrasound has limited prognostic value .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 It was found that postsurgical pathology diagnosis concurred with 48.4% of preoperative diagnosis determined by US. Increased white blood count may suggest acute bacterial infection such as lymphadenitis.…”
Section: Evaluation Of Neck Masses In Childrenmentioning
confidence: 71%
“…Increased white blood count may suggest acute bacterial infection such as lymphadenitis. 9 US is the preferred imaging modality for diagnosing thyroglossal duct cyst compared with computed tomography (CT) because of its ability to differentiate thyroglossal duct cysts from other cervical masses. An ultrasound (US) is commonly used initially in children because of being the least invasive.…”
Section: Evaluation Of Neck Masses In Childrenmentioning
confidence: 99%